Modelling the H olocene migrational dynamics of F agus sylvatica L. and P icea abies ( L .) H . K arst - Doerte Lehsten; Stefan Dullinger; Karl Hülber; Guy Schurgers; Rachid Cheddadi; Henri Laborde; Veiko Lehsten; Louis François; Marie Dury; Martin T. Sykes (Global Ecology and Biogeography, 2014)
Aim Vegetation dynamics and the competitive interactions involved are assumed to restrict the ability of species to migrate. But in most migration modelling approaches disturbance‐driven succession and competition processes are reduced to simple assumptions or are even missing. The aim of this study was to test a combination of a migration model and a dynamic vegetation model to estimate the migration of tree species controlled by climate, environment and local species dynamics such as succession and competition. Location E urope. Methods To estimate the effect of vegetation dynamics on the migration of E uropean beech and N orway spruce, we developed a post‐process migration tool ( LPJ‐CATS ). This tool integrates outputs of the migration model CATS and the dynamic vegetation model LPJ‐GUESS . The model LPJ‐CATS relies on a linear dependency between the dispersal kernel and migration rate and is based on the assumption that competition reduces fecundity. Results Simulating potential migration rates with the CATS model, which does not account for competition and disturbance, resulted in mean Holocene migration rates of 435 ± 55 and 330 ± 95 m year −1 for the two species P icea abies and F agus sylvatica , respectively. With LPJ‐CATS , these mean migration rates were reduced to 250 ± 75 and 170 ± 60 m year −1 for spruce and beech, respectively. Moreover, LPJ‐CATS simulated migration pathways of these two species that generally comply well with those documented in the palaeo‐records. Main conclusions Our ‘hybrid’ modelling approach allowed for the simulation of generally realistic Holocene migration rates and pathways of the two study species on a continental scale. It suggests that competition can considerably modify spread rates, but also the magnitude of its effect depends on how close climate conditions are to the niche requirements of a particular species.

Revisiting tree-migration rates: Abies alba (Mill.), a case study - Rachid Cheddadi; H. John B. Birks; Pedro Tarroso; Sascha Liepelt; Dusan Gömöry; Stefan Dullinger; Eliane S. Meier; Karl Hülber; Luigi Maiorano; Henri Laborde (Vegetation History and Archaeobotany, 2014)